Clinical Evaluation of Afﬁrm VPIII in the Detection and Identiﬁcation of Trichomonas vaginalis, Gardnerella vaginalis, and Candida Species in Vaginitis/Vaginosis - Haywood L. Brown; Deanna D. Fuller; Lori T. Jasper; Thomas E. Davis; Justin D. Wright (Hindawi Limited, 2004)
Objective: To compare the Affirm VPIII Microbial Identification Test for detection and identification of Candida species, Gardnerella vaginalis and Trichomonas vaginalis to clinical and microscopic criteria commonly used to diagnose vaginitis.